Determining the Symptoms of Long-COVID-19 Infection in COVID Long-Haulers - Pellino, Stefania; Luciano, Margherita; Luciano, Rosamaria; Mancini, Erika; Conte, Maria Concetta; Volpe, Gennaro; Zerella, Tommaso (New Advances in Medicine and Medical Science Vol. 8, 2023)
This chapter highlights about Long-COVID-19 Symptoms after Infection in COVID Long-Haulers. The scientific community and healthcare professionals are faced with the dilemma of not only understanding diverse ways in which SARS-CoV-2 affects the host cells but also the capability of the virus in exerting prolonged enervating organ effects after an acute-phase SARS-CoV-2 infection in COVID-19. The risk of transmission from a SARS-CoV-2 infected individual varies with the type and duration of exposure, the use of preventive measures, and the likely individual factors. The results of the molecular swab may not indicate that the body and mind have fully recovered; patients may still have symptoms months after contracting Sars-CoV-2. Patients who have recovered from COVID-19 typically have the following symptoms between 6 and 12 months after their diagnosis: asthenia, dyspnea, difficulties breathing deeply, myalgia, psychological issues, and difficulty concentrating, such as "brain fog". The study was conducted from June 2021 to July 2021 at Health Prevention Department in Benevento (Campania Region, South Italy). 133 patients accepted the questionnaire in the form of a telephone interview. Pulmonary and cardiovascular manifestations were more frequently in patients with diabetes, bpco, and hypertension. Psychological symptoms, such as anxiety and depression, were more frequently in adolescent patients and the same in female gender. Researchers will learn more about how and why the coronavirus affects different people in such a variety of ways, and why some people experience no symptoms at all while others have life-threatening organ damage or lasting disability.